What am I to action learning and what is action learning to me?. (1st September 2016) - Doherty, Daniel
ABSTRACT: This account of practice charts one organisation development practitioner's experience of the influence of action learning (AL) at various points in his career, from the early 1970s to the present day. It explores the impact of AL upon his practice over the years, chronicling various episodes which had strongest impact. It contrasts AL as it was in its formative years in the UK with how it is now, asking some questions as to how the early pioneering spirit might sustain the face of forces for commoditisation.